Longevity of total hip arthroplasty implants in patients with Gaucher disease. Issue 2 (March 2020) - Cohen, Daniel; Kogan, Dina; Rubin, Amir; Zimran, Ari; Lebel, Ehud
Background: Total hip replacement (THR) is performed for arthritic hip joints, which in Gaucher disease results from osteonecrosis of the femoral head. This procedure was recommended as valid and safe for this group of patients. Nevertheless, long term outcome has not been evaluated in a large cohort. Methods: Data regarding all patients having hip replacement in a relatively large Gaucher clinic was collected. Specifically, details such as patient background and quality of life, implant types, radiographic signs of implant-loosening, and success of implant revision were gathered. Results: The cohort included 48 patients (females 42%, mean age at operation 42 ± 14 years), having 54 hip implants. 15 years survival was 60% and an average implant life was 12.8 years. Longevity was related to implant type, with cementless implants using ceramic-on-ceramic bearing surfaces performing better than other types (no revisions so-far). Older age at surgery also involved a lower revision risk. Gender, disease genotype, and use of cement during the procedure did not have significant effect on longevity. As expected, quality of life and hip related function were better for patients who did not undergo revision. This implies the importance of long-term implant survival Conclusion: Based on these results we recommend THR as a viable treatment for symptomatic hip arthrosis, especially at older age. Specifically, the utilisation of ceramic on ceramic bearing surfaced shows promising result in patients with Gauchers disease.